LIFE CYCLE OF HELMINTH INFECTIONS IN HUMANS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Giardiasis is an intestinal infection primarily affecting the small intestine, caused in humans by the single-celled parasite Giardia intestinalis. There is no international classification for giardiasis; foreign authors focus on different forms of the disease (acute, subacute, chronic) and identify complications associated with giardiasis, including gastrointestinal disorders, extraintestinal manifestations, arthritis, and dermatological and ocular symptoms.